2015
DOI: 10.1007/s00468-015-1327-8
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variation of wood density, stiffness and microfibril angle along Eucalyptus trunks grown under contrasting growth conditions

Abstract: International audienceFew studies have investigated the influence of environmental conditions on the within-treevariation in Eucalyptus wood traits. The genotype and environment effects and their interactionsinfluence the wood properties. Their evaluations are crucial to estimate the genotype values andto select with efficiency. Thus, the aim of this study was to better understand the effect ofground slope and wind speed on the spatial variation of basic density (ρ), stiffness (MOE) andmicrofibril angle (MFA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 29 publications
2
9
0
2
Order By: Relevance
“…Donaldson (2008) reiterates, however, that unlike conifers, in Eucalyptus wood, the MFA is smaller near the pith, with a typical range from 15° to 20°. The high coefficient of variation observed for MFA shows that the variation pattern found corroborates patterns in previous research, such as those described for Eucalyptus grandis (Ramos et al 2011, Lima et al 2014, E. nitens (Medhurst 2012) and hybrids of E. grandis × E. urophylla (Hein et al 2015).…”
Section: Variation Of the Wood Properties In The Pith-bark Directionsupporting
confidence: 90%
See 1 more Smart Citation
“…Donaldson (2008) reiterates, however, that unlike conifers, in Eucalyptus wood, the MFA is smaller near the pith, with a typical range from 15° to 20°. The high coefficient of variation observed for MFA shows that the variation pattern found corroborates patterns in previous research, such as those described for Eucalyptus grandis (Ramos et al 2011, Lima et al 2014, E. nitens (Medhurst 2012) and hybrids of E. grandis × E. urophylla (Hein et al 2015).…”
Section: Variation Of the Wood Properties In The Pith-bark Directionsupporting
confidence: 90%
“…The increase in FL and BD, followed by subsequent stabilization of values close to the bark, for both or just one of the properties, is a pattern commonly described for woody species, and results mainly from the juvenile wood formation in the early years of plant growth, which over time tends toward stabilization as the wood reaches maturity (Tomazello-Filho 1987, Bhat et al 1990. A similar variation pattern for FL was also recently described by Palermo et al (2015) to determine the limits between adult and juvenile wood of Eucalyptus grandis wood, and for increasing behavior of BD by Hein et al (2015) who studied the effect of terrain slope and wind velocity on the BD and other Eucalyptus grandis hybrids × E.urophylla wood properties. Melo et al (2016) also observed a significant radial increase in fiber length and basic density in Eucalyptus spp.…”
Section: Variation Of the Wood Properties In The Pith-bark Directionsupporting
confidence: 75%
“…They found a positive relationship between fiber length and fiber wall thickness with radial position and a negative relation between vessel diameter and ray frequency with the radial position. Hein et al (2016), testing a 6-year-old Eucalyptus grandis x E. urophylla hybrids growing in three contrasting growing conditions influenced by ground slope and wind regime, found that pith-to-bark variations in wood density, MFA and MOE is more consistent than those along the trunk. Wood density, MFA and MOE have lower tree top variation because these woods were recently produced, few months before harvesting.…”
Section: Spatial Variation Of Wood Properties Along Stemmentioning
confidence: 99%
“…O incremento da massa específica no sentido radial é comumente verificado para diferentes espécies, com destaque para as de rápido crescimento (Mattos et al, 2011;Melo et al, 2013;Machado et al, 2014;Melo, 2015;Hein et al, 2016).…”
Section: Conclusãounclassified